Selective transepithelial ablation with simultaneous accelerated corneal crosslinking for corneal regularization of keratoconus: STARE-X protocol. Issue 11 (November 2021) - Rechichi, Miguel; Mazzotta, Cosimo; Oliverio, Giovanni William; Romano, Vito; Borroni, Davide; Ferrise, Marco; Bagaglia, Simone; Jacob, Soosan; Meduri, Alessandro
Abstract : Selective transepithelial ablation for regularization of cornea and simultaneous crosslinking improved both visual acuity and corneal aberrations after 2 years. Corrected distance visual acuity and spherical aberration were significantly reduced in peripheral cone patients. Abstract : Purpose: To evaluate the changes in refractive outcomes and corneal aberrations in central and paracentral keratoconus after selective transepithelial topography-guided photorefractive keratectomy combined with accelerated corneal crosslinking (STARE-X). Settings: Centro Polispecialistico Mediterraneo, Siena Crosslinking Center, and University of Messina, Italy. Design: Prospective, interventional, multicentric study. Methods: Patients were subdivided into 2 groups: Group 1 with cone located within the central 3 mm zone (50 eyes) and Group 2 (50 eyes) with cone located outside the central 3 mm zone. Follow-up was 2 years at least for all eyes. Outcome parameters included uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA). Corneal tomography and corneal wavefront aberrations were assessed and compared before and 2 years after the treatment. Results: 100 eyes of 100 patients underwent STARE-X protocol. At 2 years, UDVA and CDVA improved, and sphere, cylinder, and Kmax reduced after treatment in both groups ( P < .001, respectively). Moreover, a statistically significant reduction was observed of total higher-order aberrations root main square (RMS), coma RMS, and spherical aberration RMS in both groups ( P < .001, respectively). However, CDVA improved more in Group 1 than in Group 2 ( P < .02). Conclusions: The STARE-X protocol demonstrated effective results in halting keratoconus progression and improving corneal regularity with a safe and effective profile. STARE-X improved both visual acuity and corneal aberration at 2 years. Longer follow-up studies are warranted to observe further long-term CXL flattening effect on the cone.